Prostorska predstava študentov Fakultete za arhitekturo v Ljubljani - Kušar, Domen (AR. Arhitektura, raziskave, 2004)
Depending on numerous factors, spatial abilities of students, enrolling in the Faculty of architecture, differ. For several years students have undertaken two tests on spatial ability within the course Descriptive geometry. The so-called mental rotating test was used in the test, which is one of the generally accepted tests for establishing spatial ability. The first test is conducted in October, before course work begins, while the second test is done alongside the written examination in June or September, after a year of architectural studies. The results are interesting and comparable to similar research. Differences according to gender are very evident. Male students have better developed spatial ability than female students. Intensive work in first year courses, which help in developing spatial ability, have positive effects and undoubtedly point out improvements. The second finding, established from comparison of the October results between enrolled regular and part-time students, confirmed the objectivity of entrance exams. at least from the aspect of spatial ability.
Keywords: prostorska predstava; opisna geometrija; testi; študentje; Fakulteta za arhitekturo